Research of surface activating influence on formation of adhesion between gas-thermal coating and steel substrate; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Kovalevskaya Zh. G. Zhanna Gennadievna (Innovative technologies for producing and machining materials in mechanical engineering, 2015)
Title screen